AN INNOVATIVE APPROACH TO CLEANING COTTON LINTERS - Azambayev, Mukhammadjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The review of scientific research works devoted to the improvement of the linterization process is devoted to the analytical analysis of literary sources and the current state of technology and technology of the linterization process. This article analyzes the results of research conducted to improve the designs of linter machines.